2011
DOI: 10.1021/ef2006707
|View full text |Cite
|
Sign up to set email alerts
|

Network Modeling of Gas Trapping and Mobility in Foam Enhanced Oil Recovery

Abstract: Foam greatly reduces the mobility of gas in porous media, both by increasing the effective viscosity of the gas phase and by trapping a substantial fraction of the gas in place. Mechanistic models for foam mobility split the effect of foam into an effective viscosity and an effective relative permeability, which includes the effect of gas trapping. The effective gas relative permeability is represented as a function of the volume fraction of gas that flows, which depends on the pressure gradient. We test vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…(v) Real porous media are of course not bundles of capillaries and it is obvious that this model is not the most realistic one and is therefore unable to take into account nonlinear opening up of pores especially in the vicinity of the yield pressure gradient (Balhoff et al 2012). This is a result of a complex percolation pattern only predictable by solving the pore-level physics (Balan et al 2011). The use of more complex models for porous media such as pore networks would imply the necessity of knowing more details regarding the pore geometry and connectivity (coordination number, pore body-to-pore throat aspect ratio, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…(v) Real porous media are of course not bundles of capillaries and it is obvious that this model is not the most realistic one and is therefore unable to take into account nonlinear opening up of pores especially in the vicinity of the yield pressure gradient (Balhoff et al 2012). This is a result of a complex percolation pattern only predictable by solving the pore-level physics (Balan et al 2011). The use of more complex models for porous media such as pore networks would imply the necessity of knowing more details regarding the pore geometry and connectivity (coordination number, pore body-to-pore throat aspect ratio, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in previous studies, the yield stress behavior of stationary lamellae was studied on the pore-scale level (5,18,19,20). Some authors also considered yield stress as a fixed parameter depending on the ratio of surface tension to pore throat, considering the porous media as a bundle of capillary tubes (21,22). Others (23,24,25) presented foam in low permeability consolidated porous media as a yield stress fluid, which was also described by a threshold pressure (26).…”
Section: Introductionmentioning
confidence: 99%
“… 38 It has been demonstrated that the solubility of methane in crude oil is much greater than the solubility of nitrogen in crude oil, which means that after the methane bubble bursts, part of the methane is inefficiently displaced and part of the methane is trapped in the formation. 39 However, part of the methane gas easily dissolves in the crude oil under high pressures, forming foam oil, which causes the density and viscosity of the crude oil to decrease. This facilitates the flow of crude oil during the displacement process, resulting in higher oil recovery.…”
Section: Resultsmentioning
confidence: 99%